2022
DOI: 10.3390/jcm11102898
|View full text |Cite
|
Sign up to set email alerts
|

Callosal Angle Sub-Score of the Radscale in Patients with Idiopathic Normal Pressure Hydrocephalus Is Associated with Positive Tap Test Response

Abstract: The aim of the present study was the implementation of the composite imaging “Radscale” in patients with idiopathic normal pressure hydrocephalus (iNPH) and the evaluation of its score, as well as absolute stroke volume and peak flow velocity of cerebrospinal fluid (CSF) in aqueduct as indicators of a positive response following a tap test. Forty-five patients with iNPH were included. Clinical evaluation involved the 10 m timed walk test before and every 24 h for 3 consecutive days after evacuative lumbar punc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
(61 reference statements)
1
5
0
Order By: Relevance
“…Laticevschi et al, (2021) found that Radscale total score was similar between tap test responders and non-responders [104]. This finding was confirmed by another recent study that implemented Radscale on iNPH patients' brain MRIs [80].…”
Section: Imaging Markers Of Inph With Possible Prognostic Valuesupporting
confidence: 53%
See 3 more Smart Citations
“…Laticevschi et al, (2021) found that Radscale total score was similar between tap test responders and non-responders [104]. This finding was confirmed by another recent study that implemented Radscale on iNPH patients' brain MRIs [80].…”
Section: Imaging Markers Of Inph With Possible Prognostic Valuesupporting
confidence: 53%
“…Regarding the association of imaging markers with the severity of symptoms, tap test, and shunt responsiveness, the following conclusions can be drawn. EI and CA have been, according to many studies, correlated to both tap test and shunt responsiveness [16,[79][80][81]85]. Nevertheless, CA failed to predict shunt responsiveness according to Skalický et al, (2021) [83].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Radiologically, it is characterized by enlarged lateral and third ventricles, disproportionally to cortical sulci enlargement, as depicted by brain imaging, either with computed tomography (CT) or magnetic resonance imaging (MRI) [ 8 ]. Increased Evans index, temporal horns dilation, periventricular white matter lesions, narrow callosal angle and sulci in the convexity, focally enlarged sulci and dilated Sylvian fissures are additional imaging findings that have been described [ 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 98%